YOUTUBE: TROBOSAN MEDIA PEMBELAJARAN EKONOMI BAGI MAHASISWA - Luhsasi, Dwi Iga; Sadjiarto, Arief (UNIVERSITAS NEGERI SURABAYA, 2017)
This study starts from the problem of the using of technology-based learning media. Nowadays, this media more needed. Why? Because students more like learn using the technology than using the conventional method. But the utilization of economic-accounting learning media not being used optimally. There are economic-accounting learning media on YouTube have no interesting content. Contents that show on YouTube are about the hobby and art. So, the aim of this study is to know the properness of technology-based learning media development on YouTube. The subjects of this study are 2 expert test subjects and 24 trial test subjects. Trial test subjects are students of Economic Education FKIP UKSW. The result of this study is technology-based learning media can be used by students. This media proper as economic-accountings learning media. Hopefully, in the future studies can be able to improve the economic-accounting learning media on YouTube.